Translate the sentence into an equation.
Two less than the product of 8 and a number equals 6.
Use the variable y for the unknown number.

Respuesta :

Answer:

The expression of the given statement is 8 y - 2  = 6.

Step-by-step explanation:

Here, let the unknown number = y

Now, product of y and 8 =  8 times  y   =   8 y

Also, two less than the product    =  Product - 2

So, two less than the product  of 8 and y =  8 y - 2

Now, this above expression is equivalent to 6.

⇒8 y - 2  = 6

Hence the expression of the given statement is 8 y - 2  = 6.

ACCESS MORE